A new giant Vellozia (Velloziaceae) from Minas Gerais, Brazil with comments on the V. compacta complex and conservation - Alves, Ruy José Válka; Guimarães, Alessandra Ribeiro; Rezende, Claudia De Moraes; Braga, Laura Di Spirito; Silva, Nílber Gonçalves Da (Phytotaxa, 2014)
A new giant Vellozia species from the Ouro Branco range, Minas Gerais, is described and compared morphologically to the other dracenoid species. Leaf-anatomical characters and a unique suite of chemical constituents which help to separate the new species from V. compacta, sympatric in the range, are provided. Furthermore we discuss the circumscription of V. compacta and argue that this binomial is applied to a species complex in need of further taxonomic study.